(untitled) (Journal of Rangpur Medical College, 2026)
Background: Albuminuria and serum creatinine are key markers of diabetic kidney involvement, yet their relationship in routine secondary-care settings in Bangladesh is not well characterized. Objective: This study aimed to evaluate the association between albumin-to-creatinine ratio (ACR) and serum creatinine among diabetic patients. Methods: This cross-sectional study was conducted among 70 diabetic patients at Bangladesh Institute of Health Sciences (BIHS) General Hospital, Dhaka, from July 2024 to June 2025. Spot urine ACR, serum creatinine, fasting blood sugar, and post-breakfast blood sugar were analyzed using standard cut-offs and appropriate comparative tests. Results: Mean ACR was 655.75±1023.99 mg/g, and mean serum creatinine was 1.32±0.49 mg/dL. Moderately increased ACR was observed in 50.0% and severely increased ACR in 40.0%, while 44.3% had elevated creatinine (>1.3 mg/dL). Although the ACR category was not significantly associated with creatinine status (p=0.067), serum creatinine rose significantly across ACR categories (p=0.001). Glycaemic parameters showed no significant differences by creatinine status. Conclusion: Routine ACR screening alongside creatinine may improve early DKD detection in secondary care. J Rang Med Col.2026 Mar;11(1): 45-50